Rosuvastatin-Induced Oral Ulcer: A Case Report and Review of Literature - Metab Algeffari; Mansour Alsharidah (Case Reports in Dentistry)
Background. The benefits of prescribing statins are well published in the treatment of hypercholesterolemia. With such widespread usage of statins, physicians may be ignoring or misdiagnosing the association of oral side effects with these medications. Case Summary. A 54-year-old man presented with a painful ulceration on the dorsum of his tongue that had been recurring for 10 months. Originally, he experienced a burning sensation on his tongue, and as the lesion advanced, the pain became more intense specially when consuming spicy or acidic foods. He is on rosuvastatin for the treatment of hypercholesterolemia for over five years. Several months prior to the lesion forming, his physician increased his daily dosage of rosuvastatin from 10 mg to 20 mg. Four weeks later at a follow-up appointment, all workup did not show any significant findings, the examination revealed a new ulcer on the dorsum of the tongue, and he reported no improvement after antifungal lozenges, nor when administered a short one-week treatment with oral steroids. After eight weeks of statin discontinued, the patient showed improvement with no episodes of ulceration. Conclusion. Physicians do note that statins affect multiple immunological pathways, which could explain some adverse cutaneous reactions. More research is needed in discovering the link of statins and oral disorders.